Urethral Stricture and Stone: Their Coexistence and Management - Vashishtha, Saurabh; Sureka, Sanjoy Kumar; Agarwal, Shikhar; Srivastava, Alok; Prabhakaran, Sandeep; Kapoor, Rakesh; Srivastava, Aneesh; Ranjan, Priyadarshi; Ansari, Sulah (Urology Journal, 2014)
Abstract Purpose: The aim of the study was to determine whether the coexistence of urethral stricture and stone influence the treatment modality of each other and to ascertain the best treatment modality for these group of patients. We also tried to speculate whether the stone is an effect or a cause of the stricture. Materials and Methods: Retrospective analysis of prospectively collected data of 35 male patients with coexistent urethral stricture and stone were done between January 1998 and December 2011. Patients were divided in two groups (1 and 2) - limited stone bulk (group 1, n =30) and extensive stone bulk (group 2, n = 5). The former group was treated with endourologic procedures and the latter group managed with open staged procedures. We used ureter scope for endourological management which we think eases the management. Results: Endoscopic management of both stone and stricture were successful in all patients of group 1. Patients of group 2 have been managed by open surgery in two stages. All of them are urologically asymptomatic after a mean of 28 months of follow up. The principle of treatment modality were the bulk of stone, its location and characteristics of stricture. determinants Conclusion: Both stone and stricture can be managed successfully by endoscopic method in most of the patients. Bulk, location of the urethral stone and length of stricture is the main limiting factor for the endoscopic management. A stone can be an "effect" as well as the "cause" of strictured urethra.